Prevalence and risk factor for refractive error in rural Chinese adults in Kailu, Inner Mongolia. (26th October 2020) - Cheng, Fang; Shan, Li; Song, Wulian; Fan, Pan; Zhang, Lijuan; Wang, Xinyu; Yuan, Huiping
Abstract: Purpose: To investigate the prevalence of refractive error in adults 40 years of age and older in Kailu, Inner Mongolia. Methods: A population‐based, cross‐sectional study was conducted in Chinese adults. Spherical equivalent (S.E.) refractive error was determined from the right eye. Myopia and hyperopia were defined as a spherical equivalent (S.E.) < −0.5 dioptres (D) and >0.5 D, respectively. Since the prevalence of high myopia will vary with the precise criterion chosen, the prevalence of this condition was calculated for thresholds of both <−5.0 D and <6.0 D. Astigmatism was defined as cylinder power >0.5 D. Anisometropia was defined as a difference in S.E. between the two eyes >1.0 D. Results: The prevalence of myopia, high myopia (<−5.0 D/<−6.0 D) and hyperopia in Kailu adults was 60.3% (95%CI: 58.95–61.71), 5.5% (95%CI: 4.82–6.10) /4.0% (95%CI: 3.47–4.57) and 12.2% (95%CI: 11.26–13.11), respectively. The age‐ and gender‐standardised prevalence of myopia, high myopia (−5.0 D/−6.0 D) and hyperopia were 62.5% (95%CI: 61.05–63.99), 5.0% (95%CI: 4.34–5.61) /3.5% (95%CI: 2.99–4.04) and 10.6% (95%CI: 9.71–11.49), respectively. 52.9% had refractive astigmatism >0.5 D and 18.8% of subjects had clinically significant anisometropia. Age was significantly associated with hyperopia, high myopia, astigmatism and anisometropia. Myopia was more prevalent in females. Individuals with a higher educational level had a greater and lesser likelihood of myopia and astigmatism, respectively. Conclusions: Myopia affects around two‐thirds of the rural Chinese population over 40 years of age in Kailu. This high prevalence highlights that rural populations should be included in epidemiological studies of refractive error. Further investigations are needed to clarify the role of environmental factors in myopia development.